Avistor Shanghai Co. Ltd. : a strategy for managed industrial facilities in Shanghai. - Choo, Wee Ee. (2008)
Avistor Group, a leading business space solution provider, was set up with one of the business mission to spearhead the drive to overseas markets in the managed industrial facilities industry. To facilitate business expansion in China, Avistor China, a wholly owned susidiary of Avistor Group, was set up in Shanghai in October 2001.